153 LIMITATIONS OF DIPSTICK URINALYSIS IN DETECTING CLINICALLY SIGNIFICANT PROTEINURIA IN CHRONIC SPINAL CORD INJURY. Issue 1 (1st January 2007) - Gilless, J. P.; Greenwell, M. W.; Mangold, T. M.; Wall, B. M.
Abstract : Purpose: Proteinuria has been shown to be associated with increased all-cause mortality in the chronic SCI population. This study was designed to assess the accuracy of dipstick urinalysis in predicting clinical proteinuria (> 500 mg/dy). Methods: A retrospective analysis was performed in 219 SCI patients (99.5% male, age 54 [138} 14 years, 58% paraplegic and 42% quadriplegic, duration of injury 21 ± 14 years). Dipstick urinalysis and 24-hour urine collections were performed in each subject. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and likelihood ratios (LRs) of dipstick protein in predicting proteinuria were calculated. Results: Any level of dipstick positive proteinuria had a high specificity, PPV, and positive LR for the presence of > 0.5 g/d of proteinuria. However, the sensitivity, NPV, and negative LRs were much lower. Adjusting dipstick protein for urine-specific gravity did not improve the accuracy of dipstick protein for detecting clinically significant proteinuria. Conclusion: These data indicate that dipstick protein is a highly specific but relatively insensitive test for detecting clinical proteinuria in SCI patients, even after correction for specific gravity. Dipstick urinalysis failed to identify significant numbers of SCI patients who had clinically significant proteinuria. Future studies will focus on the utility of spot urinary protein creatinine ratios for quantitating proteinuria in this population.